Three-year survival, correlates and salvage therapies in patients receiving first-line pembrolizumab for advanced Merkel cell carcinoma. Issue 4 (20th April 2021) - Nghiem, Paul; Bhatia, Shailender; Lipson, Evan J; Sharfman, William H; Kudchadkar, Ragini R; Brohl, Andrew S; Friedlander, Philip A; Daud, Adil; Kluger, Harriet M; Reddy, Sunil A; Boulmay, Brian C; Riker, Adam; et al.
Abstract : Background: Merkel cell carcinoma (MCC) is an aggressive skin cancer associated with poor survival. Programmed cell death-1 (PD-1) pathway inhibitors have shown high rates of durable tumor regression compared with chemotherapy for MCC. The current study was undertaken to assess baseline and on-treatment factors associated with MCC regression and 3-year survival, and to explore the effects of salvage therapies in patients experiencing initial non-response or tumor progression after response or stable disease following first-line pembrolizumab therapy on Cancer Immunotherapy Trials Network-09/KEYNOTE-017. Methods: In this multicenter phase II trial, 50 patients with advanced unresectable MCC received pembrolizumab 2 mg/kg every 3 weeks for ≤2 years. Patients were followed for a median of 31.8 months. Results: Overall response rate to pembrolizumab was 58% (complete response 30%+partial response 28%; 95% CI 43.2 to 71.8). Among 29 responders, the median response duration was not reached (NR) at 3 years (range 1.0+ to 51.8+ months). Median progression-free survival (PFS) was 16.8 months (95% CI 4.6 to 43.4) and the 3-year PFS was 39.1%. Median OS was NR; the 3-year OS was 59.4% for all patients and 89.5% for responders. Baseline Eastern Cooperative Oncology Group performance status of 0, greater per cent tumor reduction, completion of 2 years of treatment and low neutrophil-to-lymphocyte ratio were associated with response and longer survival. Among patients with initial disease progression or those who developed progression after response or stable disease, some had extended survival with subsequent treatments including chemotherapies and immunotherapies. Conclusions: This study represents the longest available follow-up from any first-line anti-programmed death-(ligand) 1 (anti-PD-(L)1) therapy in MCC, confirming durable PFS and OS in a proportion of patients. After initial tumor progression or relapse following response, some patients receiving salvage therapies survived. Improving the management of anti-PD-(L)1-refractory MCC remains a challenge and a high priority. Trial registration number: NCT02267603 .